Zmiany znaczeniowe leksemu "parafianin", "parafianka" w epoce oświecenia na przykładzie czasopisma "Monitor" = Changes of meaning in the lexeme "parishioner" and "female parishioner" in the Enlightenment based on the magazine "Monitor" - Gorzelana, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the article is to present changes in the meaning of words "parishioners" and "female parishioners" in the Enlightenment. These lexemes, which derive from the word indicating a territory associated with religion as a bastion of conservatism, were applied to those who did not follow the liberal views.
Keywords: "Monitor" - czasopismo; oświecenie; parafianka; przesunięcie semantyczne; Enlightenment; "Monitor" magazine; parishioner; semantic shift